2018
DOI: 10.1002/jcp.27808
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of either C‐peptide or l‐arginine on pancreatic β‐cell function, proliferation, and oxidative stress in streptozotocin‐induced diabetic rats

Abstract: Diabetes and cardiometabolic risk factors including hypertension and dyslipidemia are the major threats to human health in the 21st century. Apoptosis in pancreatic tissue is one of the major causes of diabetes type 1 progression. The aim of this study was to investigate the effects of C‐peptide or l‐arginine on some cardiometabolic risk factors, pancreatic morphology, function and apoptosis, and the mechanisms of their actions. Forty adult male albino rats were divided into four equal groups: 1—control nondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Therefore, the rise in insulin resistance in insulin-treated patients may be due to poor glycaemic control, which in turn reduces insulin action by lowering the level of nitric oxide (Mohammad et al 2021). Previous studies have revealed that nitric oxide contributes to the effect of insulin via intracellular mechanisms (Ding et al 2000;Kocic et al 2007;Ragy and Ahmed 2019). The correlation between FSG and HO-MA-IR observed in this study further confirms the role of hyperglycaemia in increasing insulin resistance.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the rise in insulin resistance in insulin-treated patients may be due to poor glycaemic control, which in turn reduces insulin action by lowering the level of nitric oxide (Mohammad et al 2021). Previous studies have revealed that nitric oxide contributes to the effect of insulin via intracellular mechanisms (Ding et al 2000;Kocic et al 2007;Ragy and Ahmed 2019). The correlation between FSG and HO-MA-IR observed in this study further confirms the role of hyperglycaemia in increasing insulin resistance.…”
Section: Discussionsupporting
confidence: 83%
“…Our results stated that levels of pancreatic, hepatic, and renal total antioxidant capacity (TAC) were decreased significantly in the positive control group compared to the negative control group. These results are in harmony with previous studies [92][93][94] which described that total antioxidant levels in the pancreas, liver, and kidney were reduced in diabetic rats because hyperglycemia is associated with an imbalance between reactive oxygen species production and antioxidant defense mechanism. While the levels of pancreatic, hepatic, and renal total antioxidant capacity (TAC) were significantly increased (0.5 and 1.23 mg/kg) and in Metformin and Atorvastatin treated group compared to positive control.…”
Section: Totalsupporting
confidence: 91%
“…Arginine is a powerful stimulator of insulin secretion ( Ragy and Ahmed, 2019 ). Hence, nutrient use efficiency can be improved in part by enhancing concentrations of anabolic hormones in the intestine and the ensuing increase in tissue protein synthesis ( Yao et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%